PENCABUTAN PENGADUAN DALAM KASUS KEKERASAN DALAM RUMAH TANGGA PADA TINGKAT PENYIDIKAN DI KEPOLISIAN - Hendra Kesumawardhana (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTViolence in the home (KDRT) is a problem for all time, especially in today hampis any print media or electronic media mencerikatan violence in the household, such as beatings husband against wife, obscene acts / rape father or uncle or another relative of the child or nephew or other family relatives. Violence in the home (domestic violence) against the wife by her husband himself not only in the form of violence in the form of physical violence alone, but also an act which resulted in misery or suffering economic, sexual, psychological, and also includes acts do pemaksan or deprivation of liberty against law within the domestic sphere.The method used is the method of normative legal research and sociological research methods. In terms of normative legal research, the author conducted with environmental legislation and legal materials related to the title of the thesis, whereas in the case of legal research sociological writer doing research on how the effectiveness of the legal instruments in force and give legal protection against domestic violence childWith the enactment of Law No. 23 of 2004, it is expected that law enforcement against violence by husbands against wives can walk up. By doing penaggulangan in penal and non-penal. So that obstacles to the completion of the violence perpetrated by husbands against wives can be tackled.Expected legal protection for victims of domestic violence is the responsibility of all components of the nation. The legal protection is not just setting the criminal sanctions to the perpetrators, but also set about the process of the lawsuit (legal formal / event), compensation, recovery and security of the victims who had been set out in Regulation Indonesian legislation such as the Criminal Code, Act No. 35 of 2014 on the Amendment of Act No. 22 of 2002 on protection of Children and the Law No. 23 on the Elimination of violence housekeeping aiming to prevent all forms of domestic violence and provide legal protection for victims of domestic violence.Said Kuci: Domestic violence